Parent‐implemented brief functional analysis and treatment with coaching via telehealth. Issue 1 (15th December 2020) - Gerow, Stephanie; Radhakrishnan, Supriya; Davis, Tonya N.; Zambrano, Jacqueline; Avery, Suzannah; Cosottile, David W.; Exline, Emily
Abstract : We evaluated the use of parent‐implemented brief functional analyses in the home with coaching delivered via telehealth. Parents of 7 children with autism conducted functional analyses of their child's challenging behavior. For 4 participants, the brief functional analysis provided information regarding the function of the child's challenging behavior. A full functional analysis indicated a social function for 1 participant. The brief functional analysis yielded false positive results and subsequent assessment indicated an automatic function for another participant. The final participant did not engage in sufficient rates of challenging behavior to provide information regarding the function of the child's challenging behavior. Treatment evaluations occurred with 4 participants; these evaluations provided support for the results of the functional analysis. Together with previous research, the results indicate that parent‐implemented brief functional analyses, followed by additional assessment as needed, may be an effective method for assessing and treating challenging behavior via telehealth.